Mapping the Food Security Index Based on FAO’s Six Dimensions in Indonesia: A Spatial Analysis - Zulfazein Prasetya (Fakultas Pertanian, 2026)
This research evaluates Indonesia’s national food security by contrasting the current official Food Security Index (FSI), released annually by the National Food Agency (BAPANAS) using a traditional three-dimensional framework of availability, access, and utilization, with the updated 2020 Food and Agriculture Organization (FAO) framework. To reflect the growing complexity of modern food systems, the updated FAO approach incorporates three additional dimensions: stability, agency, and sustainability. Utilizing 2024 secondary data across all 38 Indonesian provinces, this study employs a quantitative methodology to map provincial FSI scores using Quantum GIS (QGIS) choropleth visualisations and uses Structural Equation Modeling – Partial Least Squares (SEM-PLS) to evaluate the statistical significance and causal relationships among the overall scores, six dimensions, and fourteen underlying indicators. The spatial mapping reveals that evaluating food security under the six-dimensional FAO model results in lower FSI scores across nearly all provinces compared to the government's traditional method, exposing critical hidden vulnerabilities in regional stability, agency, and sustainability. The visual mapping underscores a stark Java-centric developmental imbalance. Only three provinces, all located on Java island, achieved a "Very Secure" status: East Java (84.67), Central Java (78.92), and West Java (77.88). In stark contrast, provinces in Eastern Indonesia scored critically low and fell into the "Highly Vulnerable" category, with Highland Papua (8.08), Central Papua (14.51), and South Papua (16.00) ranking lowest nationwide. Statistical analysis through SEM-PLS confirms that all six FAO dimensions exert a positive, statistically significant impact on a province's FSI score, with specific dominant indicators driving each dimension. Rice production volume emerged as the primary driver for availability over raw field area, while average monthly rice prices served as the key determinant for access, highlighting economic affordability as a major barrier. Lifelong nutritional health under utilization was most heavily reflected by life expectancy at birth. For the three new dimensions, long-term stability was best indicated by historical avoidance of food insecurity; local agency was driven by the prevalence of Micro, Small, and Medium Enterprises (MSMEs) enabling community-level food processing and pricing; and agricultural sustainability was most strongly tied to the distribution of subsidized organic fertilizer. Ultimately, adopting the updated FAO framework demonstrates that Indonesia’s food security is considerably more fragile than conventional reporting suggests, confirming that stability, agency, and sustainability are essential components for accurate regional assessment.
Finalisasi 22 Juli 2026 Rudi H
Keywords: Pemetaan; QGIS; SEM; Mapping; Food Security; Ketahanan Pangan